Thorstein Veblen: The independent thinker whose contributions advanced a distinct tradition of heterodox economics - JOHN BATTAILE HALL (Brazilian Journal of Political Economy)
ABSTRACT Challenging Charles Camic’s perspective, this article argues that Thorstein Veblen’s time at the top amounted to about nineteen years; a fraction of his professional career. While drawing from and building upon challenges associable with a changing world which he faced - related to the ending of Laissez-faire and the rise of big business; the institutions initiated for prosecuting World War I; and the accompanying rise of the vested interests - Veblen’s writings effectively and propitiously provided a solid foundation for an American school of heterodox thought known as Original Institutional Economics.